2022
DOI: 10.20473/pmnj.v8i1.27649
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Postpartum Blues in Indonesia

Abstract: Introduction: The condition of postpartum blues is difficult to detect as it is still considered an instinct from a mother. Postpartum blues is a psychiatric disorder that, if left untreated, causes severe mental problems. This study aims to determine the factors that influences postpartum blues in postpartum mothers.Methods: This study used a cross-sectional method. The population in this study were mothers who gave birth at Balung Hospital. The sample obtained were 330 mothers who gave birth from January to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The variation in the number of participants involved in the study showed that 14 studies had a sample of fewer than 100 respondents, and only one study had a sample of 330 respondents [19]. The number of respondents in each study is described in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The variation in the number of participants involved in the study showed that 14 studies had a sample of fewer than 100 respondents, and only one study had a sample of 330 respondents [19]. The number of respondents in each study is described in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The number of respondents in each study is described in Table 2. The sampling technique used was dominated by non-probability sampling, namely purposive sampling, used mainly through 5 studies [14,18,19,21,23], followed by consecutive sampling by two studies [15,22], and accidental also by two studies [6,16]. Lastly, saturated sampling by 1 study is the same as total sampling also by 1 study [17,26].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations